1988
DOI: 10.1007/bf01889099
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the esophagus in patients with Acquired Immunodeficiency Syndrome

Abstract: Two patients with Acquired Immunodeficiency Syndrome (AIDS) and infectious esophagitis developed squamous cell carcinoma of the esophagus. The clinical, radiographic, and endoscopic presentations in both cases were atypical. One patient developed a focal flat lesion that imitated segmental esophagitis, and the other patient developed a superficially spreading carcinoma that mimicked diffuse esophagitis. In the setting of AIDS, a changing radiographic or endoscopic mucosal pattern requires biopsy to exclude the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Frager et al . reported development of squamous cell carcinoma in two AIDS patients with Candida esophagitis 7 . The presentations were atypical in that both developed radiographic patterns commonly found in patients with esophagitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frager et al . reported development of squamous cell carcinoma in two AIDS patients with Candida esophagitis 7 . The presentations were atypical in that both developed radiographic patterns commonly found in patients with esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…Frager et al reported development of squamous cell carcinoma in two AIDS patients with Candida esophagitis. 7 The presentations were atypical in that both developed radiographic patterns commonly found in patients with esophagitis. As esophagitis is a common complaint in this group of patients we believe a heightened awareness of the risk of malignancy is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Frager et al [105] reported two patients with AIDS and SCC in whom the radiographic appearance of the carcinoma was atypical, with the tumors resembling segmental or diffuse esophagitis. Frager et al [105] reported two patients with AIDS and SCC in whom the radiographic appearance of the carcinoma was atypical, with the tumors resembling segmental or diffuse esophagitis.…”
Section: Ymphoma and Carcinomamentioning
confidence: 99%